UJI ANTIOKSIDAN EKSTRAK ETANOL DAUN DAN KULIT BATANG MANGGIS Garcinia mangostana L. - Diniatik, Diniatik; Suparman, Suparman; Anggraeni, Dewi; Amar, Ibnu (Pharmaciana, 2016)
Antioxidant was a compound which possessed an activity as scavenger of free radicals. This study was aimed to examine the antioxidant activity of ethanolic extract from leaves and skin barks of Garcinia mangostana. Antioxidant activity were evaluated by using DPPH method for ethanolic extract in serial concentration of 800, 400, 200 and 100ug/mL. The result found that ethanolic extract of leaves and skin barks of Garcinia mangostana showed antioxidant activity with IC50 value of 674.947 ug/mL and 565.759 ug/ml, they were eleven and ten times weaker than d-Î±-tocopherol (IC50 57,114 ug/mL) which were used as a control. In conclusion, EE from leaves and skin barks of Garcinia mangostana exhibited an activity as scavenger of free radicals from DPPH.